El control contable de la Empresa Agroindustria “Bapesa” del Cantón Pueblo Viejo – 2021. - Lara Moran, Ruth Isamar (2022)
The case study is oriented to observe the shortcomings in the identification of the costs incurred by the company, in order to provide information on what decisions can be taken to minimize costs and cause profit maximization. During the development process, it is possible to observe the importance of having internal accounting controls in an organization or business structure, and how the work environment is conducted if the company has standards and policies, and the need to be updated and have technological equipment that efficiently assist in the actual reliable financial information. Among the techniques used in the case study, interviews were conducted with the business owner to directly observe the factors that turn it off and obtain information about the internal controls and accounting processes they use and how they approach accounting. Accounting information is relevant and at an early stage, this information can be uncertain and therefore less reliable. But if we want to buy time while the information gains confidence, its relevance is lost. If the information influences a decision, it is considered relevant and to be relevant, the information must be available in a timely manner and must help prediction.